Testing The Antecedents of Patient Satisfaction - Anggaraeni, Ni Made; Sitaniapessy, Arthur; Widokarti, Joko Rizkie (SEIKO : Journal of Management & Business, 2024)
This study examines the antecedents of patient satisfaction: waiting time, staff friendliness, and staff competence. The research was conducted at two community health centers (Puskesmas) in Jembrana Regency. The study population includes patients who have used the services of these health centers. The sampling technique used is non-probability sampling through purposive sampling. The sample size in this study is 130 respondents. The results of the hypothesis testing using multiple regression show that all three antecedents affect patient satisfaction. Keywords: waiting time, staff friendliness, staff competence, patient satisfaction